The threat of online gambling to low-income communities: Insights from a bibliometric analysis - Rassanjani, Saddam; Rahmi, Isramatur (Faculty of Social and Political Science, Universitas Airlangga, 2025)
Gambling has long been linked to various social issues, including poverty. In Indonesia, concerns have increased as some social assistance recipients have been found participating in online gambling. This study aims to provide a comprehensive overview of the global research landscape as to the relationship between gambling and poverty over the past decade, laying the groundwork for the development of evidence-based social policies. It employed a bibliometric approach, following the PRISMA guidelines. Data were collected from the Scopus database and analysed using VOSviewer software. The findings indicate that research on gambling is predominantly conducted by high-income countries, with limited focus on developing nations such as Indonesia. The results also support the general strain theory, which proposes that gambling among the impoverished is a response to economic hardship and social marginalisation. The study concludes that tackling gambling-related poverty requires evidence-based, cross-sector public policies that include economic empowerment, social protection, and mental health services. Furthermore, these findings highlight potential areas for further research to examine the causal relationship between poverty and gambling behaviour in developing countries.